Open Innovation: Analisis Gamification terhadap Intention of Engagement dan Brand Attitude - Felita, Caroline; Hardjono, Retno Kusumastuti (Jurnal Bisnis dan Manajemen, 2022)
This study aims to analyze the effect of gamification on the intention of engagement and brand attitude. This study also aims to identify and analyze user involvement in gamification activities as an open innovation process in the field of marketing. Questionnaires were distributed to 170 respondents and analyzed using SEM-PLS. The results of this study are the dimensions of perceived enjoyment have a positive and significant effect on the intention of engagement and brand attitude. The dimensions of perceived usefulness and perceived social influence only affect brand attitude. The perceived ease of use has no significant effect on the intention of engagement and brand attitude. In the context of user participation in open innovation, collaboration between users and Shopee does not seem to have a strong level of involvement. In the protection dimension, all games presented at Shopee Games have met the element of protection of intellectual property, which indicates an element of unique ideation as part of the sustainability of open innovation practices.